On the Subject of Testamentary Burden against the Background of German Law - Trzewik, Jacek (Review of European and Comparative Law, 2021)
The making of a last will and testament by a testator is an act in law. The testator is entitled to make specific dispositions to execute their last will, such as identifying an heir, making ordinary or vindication legacies, or appointing an executor of the will. At the same time, the number of potential aims intended to be achieved by the testator corresponds to the number of possible life situations that cannot be resolved through the testator’s dispositions regarding their estate. It is therefore necessary to equip the testator with such legal means that will allow them to achieve both material and non-material objectives. This is the role of the institution of testamentary burden. It has been regulated in the Polish legal system only superficially; therefore, the author refers to the legacy of German legislation to offer a better understanding of the solution.